Pengaruh Presepsi Dukungan Organisasi dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Wisata Bale Tani Jombang - Dias Eksa Cendekia; Lilis Sugi Rahayu Ningsih (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims of the efect perceived organizational support and work motivation on work productivity (case study on Bale Tani Jombang. The method used in this study is a quantitative research method and uses an associative analysis aproach. The results of the study show that: (1) Perception of Organizational Support has a partial and simultaneous influence on employee work productivity in Wisata Bale Tani Jombang Tourism, which means that if organizational support is given well, employee productivity will increase or vice versa, if organizational support decreases, employee productivity will also decrease. (2) Work motivation has a partial effect on the work productivity of employees of Bale Tani Jombang Tourism. This means that work motivation is influential to increase employee productivity. (3) The perception of organizational support and work motivation has a joint (simultaneous) influnce on the work productvity of employes of Wisata Bale Tani Jombang. This means that the perception of organiztional support and work moivation together contribute to increasing work productivity.